GAS WASTE: COMPOSITION, ECOLOGICAL AND TOXIC HARM, CLEANING METHODS AND TECHNOLOGY FOR WORKING WITH HAZARDOUS WASTE (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the chemical composition, ecological, and toxic impacts of gaseous wastes released by industrial enterprises, transportation, agriculture, and municipal services. It emphasizes the significance of harmful gases such as CO, CO₂, NOx, SO₂, NH₃, VOCs, and other toxic compounds, which contribute to the greenhouse effect, ozone layer depletion, acid precipitation, and smog. The study is based on literature analysis and data collected through gas chromatography, infrared spectroscopy, and other analytical methods. Effective treatment technologies, including mechanical, chemical, adsorption, catalytic, and biological methods, are analyzed and compared. Additionally, modern hazardous waste management technologies, such as thermal incineration, neutralization, hermetic packaging, and biotechnological approaches, are discussed. The results underline the need for integrated and sustainable approaches to minimize atmospheric pollution and protect human health. The article highlights the role of innovation, international cooperation, and legislative improvements in achieving effective gaseous waste management.